Representasi Kata "Pulang" Dalam Novel Pulang Karya Leila S Chudori dan Novel Pulang Karya Tere Liye - Adelia, Wirda (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The aim of this research is to find representations of the word "Pulang" in the Novel Pulang by Leila S. Chudori and the Novel Pulang by Tere Liye. This type of research is included in the qualitative research category. This research uses a comparative literature method with a qualitative description approach. The results of this research describe differences in the representation of the word "Pulang" which is the title of the two novels studied. Based on the results of research regarding "Representation of the Word Pulang in the Novel Pulang by Leila S. Chudori and the Novel Pulang by Tere Liye", the researcher concluded through comparative literary methods that the two novels studied had similarities and differences. The similarities between the two novels can be seen from the similarity of the titles, and the difference lies in the representation of the meaning of the word "Pulang" which represents the entire content of the story. In line with the theory put forward by Hall, the representation in this study tends to fall into the classification of intensive representation because it shows how a symbol or language realizes the personal goals of the speaker. (1) In the novel Pulang by Leila S. Chudori, the meaning of "Pulang" means the character's longing for his connection with his Indonesian self and with his loved ones after his wanderings in another country. This novel hints at the meaning of longing for state nationalism, citizenship and Indonesian culture itself. (2) Meanwhile in the novel Pulang by Tere Liye, the representation of the meaning of "Pulang" means self-acceptance of the past and all the sweet and bitter life that the main character has gone through. as well as being a religious spiritual symbol.